Biodiversidad fitoplanctónica en tres lagunas someras de la provincia de La Pampa, Argentina - Bazán, Graciela Inés (2014)
The shallow lake system, Luan Lauquen of semi-permanent regime, it’s located in the eastern physiographic region, biogeographical Chaco domain, in La Pampa province. The aim of this contribution is to amplify the knowledge of the composition and distribution of algal species in the Pichi Luan, Ea. Ansin and Lonco-Che shallow lakes. The samples were collected in spring season 2010 and autumn 2011. The biological samples collected were set in formaldehyde at 4%. A total of 99 taxa were identified for the three shallow lakes of which 52% were Chlorophyta, 11 % Charophyta, 18% Cyanobacteria, 8% Ochrophyta and 11% remaining Euglenozoa. In autumn the algae species richness in the three shallow lakes, was higher in relation to the spring, where Chlorophyta of the Chlorococcales Order was found widely represented, corresponding the maximum number of species to the Pichi Luan shallow lake. In autumn for Lonco-Che, the Cyanobacteria species richness is stands out, while for the same date the Euglenozoa prevails in the Pichi Luan. The diatom species are equally distributed in spring at all sampling sites. Oscillatoria subbrevis, Pediastrum boryanum var. boryanum, Scenedesmus bijuga and Cyclotella meneghiniana taxa, were common in the three shallow lakes. The highest similarity S= 37%, according to Bray Curtis, was in spring between Pichi Luan and Lonco-Che shallow lakes.